Pembuatan dan evaluasi masker gel peel-off ekstrak bekatul padi ketan merah (Oryza sativa L var. Glutinosa) menggunakan gelling agent polivinil alkohol (PVA) - Suhery, Wira Noviana; Ulfa, Rodhia; Saputri, Sandry Eka (Journal of Pharmaceutical and Sciences, 2023)
Gamma oryzanol and anthocyanin are bioactive components contained in red sticky rice bran (Oryza sativa L var. Glutinosa). These two ingredients function as natural antioxidants. Peel-off gel mask containing red glutinous rice bran extract is formulated with varying concentrations of polyvinyl alcohol F1 12%, F2 14%, and F3 16% as gelling agent. This research aims to formulate a peel-off gel mask and carry out an evaluation to obtain the best formula physically and with the highest antioxidant activity. Each formula was tested for organoleptic, homogeneity, pH value, physical stability during storage, spreading power and drying power of the preparation and skin irritation testing. The research results showed that F3 was the best formula in terms of physical and antioxidant activity with an inhibition percentage of 90.5827%. Based on one-way ANOVA analysis, there was a significant difference in antioxidant activity between peel-off gel mask formulas with a significant value of p<0.05.